Knowledge and awareness of polycaprolactone and its applications as provisional material in prosthodontic practice: A questionnaire-based survey - Kavan A Patel; Jayanti R Patel; Vilas V Patel; Sareen Duseja; Harekrishna Jayendra Raval (Wolters Kluwer Medknow Publications, 2023)
Aim: The present study was done to evaluate the knowledge and awareness of different provisional materials, especially polycaprolactone (PCL) and their application in prosthodontic practice. Setting and Design: A questionnaire based survey was carried out to assess the knowledge and awareness of PCL and its applications as provisional material in prosthodontic practice. Materials and Method: A questionnaire-based descriptive study consisting of 10 questions related to different provisional materials and their applications in prosthodontic practice was formulated on Google Forms. The link was created and circulated among the prosthodontist faculty members of various dental institutes and private practitioners of India with the use of digital platforms such as E-mail and social media. The data were collected and examined using Microsoft Excel software for statistical evaluation. Statistical Analysis Used: For this descriptive type of study, knowledge and awareness among prosthodontists across India was evaluated using Microsoft Excel software. Results: The use of PCL was known only to 20.75% of prosthodontists. Moreover, its application and indications are known to only <1% of the study participants. Autopolymerizing resin was most commonly used for the custom tray and temporary base fabrication as well as temporization in crown and bridge prosthesis, while muscle deprogrammer and surgical template were commonly fabricated in heat-cure and clear acrylic resin, respectively. Pattern resin was found to be commonly used in splinting implant impression copings. Conclusion: The use of PCL as a temporary denture base, custom tray, muscle deprogrammer, implant impression splinting, and provisional for crown and bridge and templates should be encouraged and incorporated to get benefits of its characteristic properties. Considering the overall performance of PCL, its use should be incorporated into prosthodontic research and practice.